2007
DOI: 10.1080/01635580701586762
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Supplement Use and Risk of Neoplastic Progression in Esophageal Adenocarcinoma: A Prospective Study

Abstract: The incidence of esophageal adenocarcinoma (EA) and its precursor condition, Barrett's esophagus, has risen rapidly in the United States for reasons that are not fully understood. Therefore, we evaluated the association between use of supplemental vitamins and minerals and risk of neoplastic progression of Barrett's esophagus and EA. The Seattle Barrett's Esophagus Program is a prospective study based on 339 men and women with histologically confirmed Barrett's esophagus. Participants underwent baseline and pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 59 publications
1
25
0
4
Order By: Relevance
“…An understanding and correction of these dietary factors could avert escalation of the disease in these countries. Recent studies have shown that dietary supplements of multivitamins and antioxidants significantly reduced the risk of oesophageal adenocarcinoma and markers of neoplastic progression among individuals with Barrett's oesophagus [44].…”
Section: Resultsmentioning
confidence: 99%
“…An understanding and correction of these dietary factors could avert escalation of the disease in these countries. Recent studies have shown that dietary supplements of multivitamins and antioxidants significantly reduced the risk of oesophageal adenocarcinoma and markers of neoplastic progression among individuals with Barrett's oesophagus [44].…”
Section: Resultsmentioning
confidence: 99%
“…The Seattle BE Program is a prospective study which is prospectively following 339 men and women with histologically confirmed BE. In this cohort study, use of multivitamins and single antioxidant supplements was associated with a significantly reduced risk of EAC and markers of neoplastic progression among individuals with BE [39] .…”
Section: Vitamins and Antioxidantsmentioning
confidence: 99%
“…However, there are hypes and controversies in risk assessment of nutraceutical in esophageal and gastrointestinal cancer management [173]. The several reports highlighted the trade-off between increased neoplasia in gastric cancer and the limits of nutraceuticals to reduce cancer growth [173,174].…”
Section: Cancers In the Human Body And Nutraceutical Protectionmentioning
confidence: 99%
“…The several reports highlighted the trade-off between increased neoplasia in gastric cancer and the limits of nutraceuticals to reduce cancer growth [173,174]. Still efforts are in the direction of antioxidant nutraceuticals to prevent or arrest the gastric cancer growth [175].…”
Section: Cancers In the Human Body And Nutraceutical Protectionmentioning
confidence: 99%
See 1 more Smart Citation